Peningkatan Kualitas Proses Produksi Air Minum Dalam Kemasan Melalui Pendekatan Six Sigma PT.XYZ - Aris Setyawan; Tita Talitha (Universitas Muria Kudus, 2026)
The bottled drinking water industry needs to maintain consistent product quality in order to remain competitive and comply with applicable quality standards. This study aims to evaluate the quality performance of the 19-liter gallon production process and identify the most dominant types of defects at PT XYZ. The Six Sigma method with the DMAIC (Define, Measure, Analyze, Improve, Control) approach was applied. The data were collected from November 2024 to October 2025. The results show an average DPMO value of 1,027.81 with a sigma level of 4.60. During the highest defect period, the DPMO reached 1,670.18 with a sigma level of 4.43. The most common defects were loose gallon caps and leaking gallons. The main causes were related to work procedures, supervision, and machine conditions. The implementation of Six Sigma helps the company measure process performance objectively and provides improvement recommendations to reduce defects and enhance production quality.